Microembolic Signals and Diffusion-weighted MR Imaging Abnormalities in Acute Ischemic Stroke - Kimura, Kazumi; Minematsu, Kazuo; Koga, Masatoshi; Arakawa, Ryuki; Yasaka, Masahiro; Yamagami, Hiroshi; Nagatsuka, Kazuyuki; Naritomi, Hiroaki; Yamaguchi, Takenori (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: The clinical significance of microembolic signals (MESs) detected by transcranial Doppler sonography (TCD) in acute ischemic stroke remains unclear. The purpose of the present study was to assess the findings of diffusion-weighted MR imaging (DWI) and other clinical characteristics in patients with acute ischemic stroke and MESs.METHODS: We performed TCD and DWI within 48 hours and 7 days, respectively, after stroke onset in 28 patients with acute brain infarction. The relationship between the number of MESs and DWI findings, risk factors for stroke, National Institutes of Health Stroke Scale (NIHSS) score on admission, and arterial disease was examined.RESULTS: Ten patients had MESs detected by TCD (MES group) and 18 had no MESs (control group). The frequency of hypertension, diabetes mellitus, hyperlipidemia, and smoking; NIHSS score; blood-coagulation parameters; and interval between stroke onset and DWI study did not differ between the two groups. However, arterial disease was more frequent in the MES group than in the control group. Small, multifocal ischemic lesions (<10 mm in diameter) on DWI were more frequent in the MES group than in the control group. Conventional CT and MR imaging often failed to show these lesions.CONCLUSION: Small, often asymptomatic DWI abnormalities were more frequent in patients with MESs detected by TCD and with large-vessel occlusive diseases than in stroke patients without MESs. TCD and DWI may provide early clues to the mechanism of stroke in the acute phase.